New fractional integral inequalities for differentiable convex functions and their applications - Hsu, K.-C.; Tseng, K.-L. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish some new fractional integral inequalities for differentiable convex functions and give several applications for the Beta-function.